Islam stands on the side of world peace and global justice - Mohd Yusof, Danial (Institute of Islamic Understanding Malaysia, 2006)
The appropriation of a civilizational context of Islam or "Islam Hadhari" in Malaysia is based on the Islamic reality of a comprehensive human, social, and national development and importantly, as a reference of the magnanimity of the Muslim polity to the rest of the world. Amongst its objectives are to produce individuals with spiritual, moral, and competitive strengths, as well as the innovation and competency to solve challenges with reason and practicality under the guidance of wisdom and peace. The principles of this policy includes a government which stand for justice and integrity, a balanced development of the economy, quality of life, a people with a senso of freedom, championing the rights of women and minority groups, moral and cultural strength, environmental conservation and military capabilities.